Analisis Pengaruh Lingkungan Organisasi, Budaya Organisasi, Beban Kerja terhadap Kinerja Karyawan - Andreas, Andreas; Sugiharti, Sugiharti (Forum Kerjasama Pendidikan Tinggi, 2024)
The purpose of this study was to understand the behavioural impact analysis of organisational environment and organisational culture and workload on employee performance. This research was conducted at Warung Makan Bebek and Ayam Kampung Mas Budi in Semarang. Research data were collected through questionnaires given to 52 respondents. This research methodology uses a quantitative research approach using a descriptive approach. In conclusion, the research findings show that organisational environment has a negative impact and has no significant effect on employee working hours with a result of -0513 with a sig value of <0.60 and >0.05, on the other hand, organisational culture has a positive impact and has no significant effect on employee working hours and a result of 2.062 > with a sig value of 0.045 and >0.05, and finally, workplace organisational environment has a positive impact and has a significant effect on employee working hours and a result of 4.221 > with a sig value of 0.001 and <0.05. Furthermore, in terms of improving employee performance, workload has a good value in improving employee performance. In particular, it is very important to improve the quality of workload and have the ability to handle work-related stress effectively. The implications of this study are very important for management in any business, and it is necessary to develop good strategies to maximise employee work through the need to maintain organisational integrity, Organisational Culture, and Workload for the duration of the business.